핵백내장에서 파장가변 빛간섭단층촬영계를 이용한 굴절력 예측의 정확성 - 안영주(Youngju An), 김효진(Hyojin Kim), 주천기(Choun-Ki Joo) (Daihan angwa haghoi jabji, 2019)
목적: 핵백내장에서 파장가변 빛간섭단층촬영계(ARGOS)를 이용한 굴절력 예측의 정확성을 평가하고자 하였다. 대상과 방법: 핵백내장으로 진단받은 107안을 대상으로 Pentacam HR로 측정한 최대 핵 밀도(maximum nuclear density)에 따라 세 그룹(A, 하위; B, 중위; C, 상위)으로 나누어 IOLMaster와 ARGOS로 측정한 각막굴절력과 안축장을 비교하였다. 최대 핵 밀도와 두 기기 간의 안축장 차이의 상관성을 평가하였고, 수술 2개월 후 자동굴절검사를 이용하여 측정한 최종 굴절력에서 예상 굴절력을 뺀 차이의 절대값으로 오차를 계산하였다. 결과: 최대 핵 밀도는 그룹 A, B, C가 각각 28.31 ± 7.30, 51.37 ± 7.82, 88.63 ± 11.23이었다. IOLMaster와 ARGOS에서 측정된 안축장은 그룹 B와 C에서 IOLMaster가 ARGOS에 비해 유의하게 길게 측정되었고(각각, p=0.035, p<0.001), 최대 핵 밀도와 두 기기 간 안축장 차이는 유의한 양의 상관성을 보였다(p<0.001). 각각의 기기에서 측정된 생체계측치에 대한 평균절대오차는 그룹 A에서 유의한 차이를 보이지 않았으나(p=0.064), 그룹 B와 C에서 ARGOS (0.31 ± 0.22D, 0.32 ± 0.20D)를 이용하여 계산된 평균절대오차가 IOLMaster (0.43 ± 0.21D, 0.50 ± 0.26D)에 비하여 유의하게 낮았다(각각, p=0.027, p=0.001). 결론: 파장가변 빛간섭단층촬영계를 이용하여 생체계측을 시행하였을 때, 중등도 이상의 핵백내장에서도 정확한 굴절력 예측이 가능하였다. Purpose: To evaluate the accuracy of predicting refractive outcomes of swept-source optical coherence tomography based biometry (ARGOS; Movu Inc., Santa Clara, CA, USA) in nuclear cataracts. Methods: A total of 107 eyes (107 nuclear cataract patients) were analyzed. Subjects were divided into three groups according to the maximum nuclear density of Pentacam HR (A, lower tertile; B, medium tertile; C, upper tertile). The keratometry and axial length measured by IOLMaster (Carl Zeiss Meditec, Jena, Germany) and ARGOS systems were compared for each group. The correlation between maximum nuclear density and axial length difference readings from the two instruments was evaluated. The mean absolute error between the predicted refraction and 2-month post-operative refraction was compared. Results: The maximum nuclear densities were 28.31 ± 7.30, 51.37 ± 7.82, and 88.63 ± 11.23 for groups A, B, and C, respectively. The axial length measured by ARGOS was significantly longer than that obtained using IOLMaster for groups B and C (respectively, p = 0.035, p < 0.001). A significantly positive correlation was found between the maximum nuclear density and axial length difference of the two devices (p < 0.001). Mean absolute errors were not significantly different between IOLMaster and ARGOS in group A. However, in groups B and C, the mean absolute error using ARGOS (0.31 ± 0.22 D and 0.32 ± 0.20 D, respectively) was significantly lower than that of IOLMaster (0.43 ± 0.21 D and 0.50 ± 0.26 D, respectively) (Group B, p = 0.027; Group C, p = 0.001). Conclusions: Even in dense nuclear cataracts, accurate refractive outcome prediction was possible using swept-source optical coherence tomography based biometry. KCI Citation Count: 0